2007
DOI: 10.1016/j.jaci.2007.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of MUC5AC in the pathogenesis of exercise-induced bronchoconstriction

Abstract: Background: The pathogenesis of exercise-induced bronchoconstriction (EIB) involves the release of mediators from several airway cells in response to exercise challenge, but the mechanism leading to airflow obstruction during EIB is incompletely understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 44 publications
2
36
0
1
Order By: Relevance
“…The average time between baseline and post-exercise-induced sputum visits was 9.3 days (range, 4-18 d) in the asthma group, and 10.0 days (range, 5-19 d) in the control group. The levels of the eicosanoids (CysLTs, 15S-HETE, and PGE 2 ) were previously reported in the asthma group (8,29), and are compared with levels of eicosanoids in the control group in Figures E1 and E2 of the online supplement.…”
Section: Subject Characteristics and Eicosanoid Levelsmentioning
confidence: 99%
“…The average time between baseline and post-exercise-induced sputum visits was 9.3 days (range, 4-18 d) in the asthma group, and 10.0 days (range, 5-19 d) in the control group. The levels of the eicosanoids (CysLTs, 15S-HETE, and PGE 2 ) were previously reported in the asthma group (8,29), and are compared with levels of eicosanoids in the control group in Figures E1 and E2 of the online supplement.…”
Section: Subject Characteristics and Eicosanoid Levelsmentioning
confidence: 99%
“…Exercise-induced bronchoconstriction (EIB) is a prototypical feature of indirect AHR in asthma that occurs in about 30 to 50% of subjects with asthma in cross-sectional studies (2,3). Prior studies have identified epithelial shedding into the airway lumen and increased production of inflammatory eicosanoids such as leukotrienes in the airways of patients with EIB (4)(5)(6)(7)(8). The basis for the dysregulation of eicosanoids in asthma is incompletely understood.…”
mentioning
confidence: 99%
“…Two polymeric mucins (MUC5AC and MUC5B) are normally expressed and secreted in the lungs by secretory cells in the conducting airway epithelium and submucosal glands, respectively. Increased production of MUC5AC mRNA and protein occurs in the airway epithelium and secretions of patients with asthma (7)(8)(9)(10), and MUC5B concentrations are increased in the secretions of patients with chronic obstructive diseases (11). Studies from several laboratories have shown that secretory mucin gene expression is up-regulated in lung epithelial cells in vitro by inflammatory/immune response mediators that are activated in the respiratory tract in response to airborne challenges and mechanisms whereby mediators up-regulating mucin gene expression have been identified (6,12,13).…”
mentioning
confidence: 99%